Paradigma Manusia dan Implikasinya terhadap Prinsip Belajar: Telaah Kajian Qur'ani - Hadi Mutamam (Institut Agama Islam Negeri (IAIN) Samarinda, 2013)
Man was created by God more perfect than others and being able to make man through education. Then the heart of the Prophet of Allah add skills over the talent he has. God made the means of communication among humans. Therefore, the substance that creates an inanimate object could be a tool to communicate. Surely no man made trouble for him (Muhammad) can read and give an explanation and teaching, and his companions were developed and forwarded by the Ulul Albab, scholars and researchers.